Policy Conflicts in The Legality of Alcohol Investment Licenses: An Advocacy Coalition Framework Perspective - Septian, Esa; Wulandari, Septi; Pratama, Obi (Jurnal Administrasi Publik (Public Administration Journal), 2024)
The phenomenon of policy conflicts that emerge in society and policy change requires an examination of the policies that are the focus of this research. With a focus on the dynamic nature and process of stakeholder-generated policies, identification is conducted over the long term, emphasizing conflict. The alcohol investment policy generated many pros and cons, prompting the government to intervene and later cancel the policy. When considering the identification of policy conflicts through the lens of the Advocacy Coalition Framework, it is important to examine the severity and speed of policy change. The findings of this study show that investment policies only fulfill economic requirements, ignoring all other considerations and standards. To support the social fabric of society, policy regulations are needed that accommodate all interests and produce win-win solutions. From upstream to downstream, alcohol circulation can be regulated using a comprehensive strategy. Policy conflicts are evaluated based on their nature, intensity, and causes through the lens of context and events.